Rancang Bangun Aplikasi Web Kalkulator Kalori Berbasis Dataset USDA untuk Pemantauan Nutrisi Harian - Ni Putu Dita Ariani Sukma Dewi; Jiyestha Aji Dharma Aryasa; Sulin Monica Putri (Jurnal Teknologi Terpadu, 2026)
This study aims to design and build a calorie calculator web application based on the Food and Nutrient Database for Dietary Studies (FNDDS) dataset from the United States Department of Agriculture (USDA) as a tool for daily nutrition monitoring. The research method uses the Waterfall system development model, which includes needs analysis, system design, implementation, testing, and evaluation. The application is built in Python using the Flask framework and utilizes the Pandas library for nutrition data processing. The system is tested using black-box testing across all key features, including food search, category selection, and nutritional content calculation. The test results showed that all system functions ran with a 100% success rate in the functional test scenario and in the calorie, protein, fat, and carbohydrate calculations, according to USDA reference data. The average system response time is less than 1 second per request, indicating efficient application performance. The novelty of this study lies in integrating the scientifically standardized USDA dataset into a lightweight Python Flask-based web application specifically designed for the educational and daily nutrition-monitoring needs of users in Indonesia, with a weight-based approach to proportional nutrition calculation. This application is expected to become a web-based nutrition education medium that is easily accessible and further developed.